ANALISIS PROGRAM PEMBERDAYAAN KAMPUNG BINAAN KELUARGA SAKINAH (KBKS) DI KAMPUNG BUANTAN LESTARI KECAMATAN BUNGA RAYA KABUPATEN SIAK - Fajar Alan Syahrier (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2024)
The Kampung Binaan Keluarga Sakinah (KBKS) Empowerment Program in Buantan Lestari Village, Bunga Raya District, Siak Regency, is an initiative to improve the welfare and empowerment of the local community. This research aims to conduct an in-depth analysis of the effectiveness and impact of the program implementation. The research method used is descriptive qualitative method. Data was collected through interviews with relevant parties, direct observation in the field, and analysis of documents related to the program. The results showed that the KBKS program was carried out in the form of skills training, religious education, and local potential development. The existence of active community participation in various program activities shows the high level of awareness and enthusiasm of residents towards empowerment. The KBKS program also makes a positive contribution to increasing the community movement that lays the foundation for the framework and agenda of socio-cultural development reform in an effort to create a community of faith and devotion.